PENGARUH HEDONIC SHOPPING VALUE DAN SHOPPING LIFESTYLE TERHADAP IMPLUSE BUYING PADA PENGGUNA APLIKASI TIKTOK MAHASISWA MANAJEMEN UNIVERSITAS MUHAMMADIYAH BENGKULU - Ardita Oktaviana Rizki; Ade Tiara Yulinda (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the influence of Hedonic Shopping Value and Shopping Lifestyle on Impulse Buying among TikTok application users who are Management Students at Muhammadiyah University of Bengkulu, both partially and simultaneously. There are several independent variables (x) to be discussed in this research, including Hedonic Shopping Value and Shopping Lifestyle. The research object is TikTok application users who are Management Students at Muhammadiyah University of Bengkulu, totaling 108 respondents. Several data analysis techniques are used in this study, including instrument testing, classical assumption testing, respondent response analysis, multiple linear regression analysis, and the coefficient of determination. also test the hypothesis. From the results of multiple linear regression tests, the regression equation obtained is as follows: 1. The research results indicate that the Hedonic shopping value variable significantly affects Impulse buying among TikTok application users at Muhammadiyah University of Bengkulu's Management students. 2. The research results indicate that the Shopping lifestyle variable significantly affects Impulse buying among TikTok application users at Muhammadiyah University of Bengkulu's Management students. 3. The research results indicate that the Hedonic shopping value and Shopping lifestyle variables significantly affect Impulse buying among TikTok application users at Muhammadiyah University of Bengkulu's Management students. Keywords: : Hedonic shopping value  , Shopping lifestyle  , Customer Satisfaction